Investigation of silicon carbide thin films properties at the open cosmos space - Y.N. Gorelov; A.V. Shcherbak; L.V. Kurganskaya; D.U. Golubeva (Физика волновых процессов и радиотехнические системы, 2017)
The problems of stability semiconductor device structures to open space conditions influence are studied. It is shown that complex investigation of electrophysical properties of semiconductor layers during the time of cosmic flight is necessary. Samples of device structures for investigation of open space conditions influence on semiconductor layer resistivity, metal-semiconductor and insulator-semiconductor interfaces properties are proposed. Methods of measuring resistivity, Hall factor, current-voltage characteristics and volt capacitive characteristics of device structures samples are considered. Measurement circuits adapted for operation with automatic measurement systems are proposed.